STUDI REALITAS WANITA KERIER DALAM MEWUJUDKAN KELUARGA SAKINAH DALAM MASYARAKAT MODERN - Nopi Pratama; Asep Wijaya (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
The existence of global changes from the agrarian era to the industrial era and even now into the information technology era, one of which has an impact on the shift in gender relations patterns. This is characterized by many women switching to the public sector or becoming career women in the hope of improving their family's economic status. The research aims to look at social changes related to career women in modern society in their role as contributors to the family economy, to create family harmony from the sociological perspective of Islamic law. The type of research used in this research is descriptive qualitative research. Through a normative-sociological approach. With data collection techniques through observation, interviews and documentation. Analysis of this research data through data reduction, data presentation, and concluding. Discussion result; 1) In the modern era, women are required to think forward and adapt to the climate of globalization and industrialization which has encouraged and spurred competency fluctuations in the world of work. 2) jobs taken by women who want to pursue a career in the public sector must also be based on family interests and by Islamic religious law. 3) To create more harmonious families in the modern era, a strong foundation of partnership between husbands and husbands is needed. and wife, complement and complement each other, and are balanced in economic terms.